THEORITICAL FOUNDATIONS OF THE INTERACTION OF SCIENCE AND SPIRITUALITY IN THE POETRY OF EMILY DICKINSON (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Our attention is directed to the emergence of a particular author’sstyle, characterized by its introspective depth, exploration of mortality andspirituality, and innovative style. Her work reflects a unique blend of mysticalintrospection and logical clarity, contributing to the gradual evolution of Americanpoetry and offering profound insights into the human experience. The articleanalyzes the relationship between science and spirituality reflecting a uniquesynthesis of rational inquiry and mystical .In addition, showing a uniquecombination of logical thinking and deep self reflection